Notes on Spinoza’s Critique of Aristotle’s Ethics: From Teleology to Process Theory - Ravven, Heidi M. (Philosophy & theology, 1989)
I argue that Spinoza’s ethical theory may be viewed as a transformation of Aristotle’s teleological account which has been corrected of several fundamental flaws which Spinoza found in Aristotle. The result of Spinoza’s redefinition of ethical activity is a developmental account of ethics which has close kinship with the views of process theoreticians.